2021
DOI: 10.1085/jgp.202012625
|View full text |Cite
|
Sign up to set email alerts
|

The molecular evolution of function in the CFTR chloride channel

Abstract: The ATP-binding cassette (ABC) transporter superfamily includes many proteins of clinical relevance, with genes expressed in all domains of life. Although most members use the energy of ATP binding and hydrolysis to accomplish the active import or export of various substrates across membranes, the cystic fibrosis transmembrane conductance regulator (CFTR) is the only known animal ABC transporter that functions primarily as an ion channel. Defects in CFTR, which is closely related to ABCC subfamily members that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 220 publications
0
13
0
Order By: Relevance
“…It specifically lacks the conserved hydrophobic residues that usually follow the phosphorylated serine in so-called “strong” PKA consensus sites and instead bears a glutamine and glutamate, both unfavored in the motif (Phosphosite Plus v. 6.6.0.2). An alignment of orthologous R domain sequences around S813 reveal that it is highly conserved among jawed vertebrates but absent in sea lamprey, suggesting it may have emerged relatively late in evolution ( Infield et al, 2021 ). However, this late emergence does not explain its lack of optimization, for example, S700 was also absent in lamprey but is fully optimized in mammals ( Infield et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It specifically lacks the conserved hydrophobic residues that usually follow the phosphorylated serine in so-called “strong” PKA consensus sites and instead bears a glutamine and glutamate, both unfavored in the motif (Phosphosite Plus v. 6.6.0.2). An alignment of orthologous R domain sequences around S813 reveal that it is highly conserved among jawed vertebrates but absent in sea lamprey, suggesting it may have emerged relatively late in evolution ( Infield et al, 2021 ). However, this late emergence does not explain its lack of optimization, for example, S700 was also absent in lamprey but is fully optimized in mammals ( Infield et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An alignment of orthologous R domain sequences around S813 reveal that it is highly conserved among jawed vertebrates but absent in sea lamprey, suggesting it may have emerged relatively late in evolution ( Infield et al, 2021 ). However, this late emergence does not explain its lack of optimization, for example, S700 was also absent in lamprey but is fully optimized in mammals ( Infield et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…(The states are labeled so that the first letter indicates whether the channel is closed [C] or open [O].) Beginning with C1a, with a single ATP bound at the first ATP binding site, which is incapable of hydrolysis ( 30 ), the reversible transition to C1b occurs when a second ATP binds so that both binding sites are occupied. Because this step involves ATP binding, the rate depends on the concentration of ATP.…”
Section: Methodsmentioning
confidence: 99%
“…The CFTR (ABCC7) protein is a member of the ABC transporter superfamily, which evolved toward the specific function of a phosphorylation-activated and ATP-gated ion channel [ 24 ]. Accordingly, as supported first by theoretical studies [ 25–30 ] and afterwards demonstrated by experimental 3D structures [ 31–35 ], CFTR shares many features of ABC transporters but exhibits specific characteristics ( Figure 1 B).…”
Section: Cftr: the Proteinmentioning
confidence: 99%
“…An additional original feature of CFTR, which is also found in other members of the ABC-C family such as MRP1, SUR1 and SUR2, is a significant divergence in the ATP-binding site 1 motif, formed by the NBD1 Walker A, Walker B and H-loop and by the NBD2 ABC signature and D-loop [ 24 ]. These non-canonical features are responsible for increased affinity for ATP and slowed ATP hydrolysis at this site [ 57 , 58 ], which is also covered by large regulatory insertion (RI), bearing a phosphorylation site.…”
Section: Cftr: the Proteinmentioning
confidence: 99%